Economic change after the agricultural revolution in Southeast Asia?. (March 2014) - King, Charlotte L.; Bentley, R. Alexander; Higham, Charles; Tayles, Nancy; Viðarsdóttir, Una Strand; Layton, Robert; Macpherson, Colin G.; Nowell, Geoff
Abstract : Three prehistoric sites in the Upper Mun River Valley of north-eastern Thailand have provided a detailed chronological succession comprising 12 occupation phases. These represent occupation spanning 2300 years, from initial settlement in the Neolithic (seventeenth century BC) through to the Iron Age, ending in the seventh century AD with the foundation of early states. The precise chronology in place in the Upper Mun River Valley makes it possible to examine changes in social organisation, technology, agriculture and demography against a background of climatic change. In this area the evidence for subsistence has been traditionally drawn from the biological remains recovered from occupation and mortuary contexts. This paper presents the results of carbon isotope analysis to identify and explain changes in subsistence over time and between sites, before comparing the results with two sites of the Sakon Nakhon Basin, located 230km to the north-east, to explore the possibility of regional differences.